BIM : inter-operability issues between BIM authoring software and structural analysis software (steel structures) - Foo, Nicholas Tun How (Nanyang Technological University, 2021)
This project highlights interoperability issues on information exchange between Building Information Modelling (BIM) authoring software and Structural Analysis (SA) software, and a proposed solution to bridge the gap. The project was done using a few software, namely Tekla Structures (TS) and Tekla Structural Designer (TSD), Microsoft Excel and Microsoft Visual Studio. Two case studies with proposed solutions were presented in this project. The first one being the information transfer of deflection from TSD to TS. Microsoft Visual Studio was used together with Tekla Open API to facilitate the information transfer process. C# coding language and Microsoft Excel spreadsheets were utilised as well. The second case study was the information transfer of utilization ratio from TSD to TS. Microsoft Excel spreadsheets and TS built-in functions were used to facilitate the information transfer process. A workflow was proposed for each case study whereby the analysis results were exported by Tekla Structural Designer to Microsoft Excel, and subsequently read back in Tekla Structures. Through this study, it is believed that by allowing freedom of information handling in the hands of civil engineers, many useful functions can be developed to improve productivity both upstream and downstream in a typical construction project. However, civil engineers themselves must also have a certain degree of understanding in both computer technologies and engineering knowledge to be fully equipped for this task. It is also easier for civil engineers to communicate with programmers by having a grasp on the functionality and limitation of computer software.